A rare case of multi-focal human TB after BCG instillation for non-muscle-invasive bladder cancer. Issue 4 (November 2020) - Riccardi, Niccolò; Ferrarese, Maurizio; Castellotti, Paola; Mazzola, Ester; Sozzi, Francesco; Rigatti, Patrizio; Vanzulli, Angelo; Sotgiu, Giovanni; Codecasa, Luigi
Objective: To describe a left epididymitis and para-aortical involvement caused by Mycobacterium tuberculosis hominis reactivation after bacillus Calmette-Guérin instillation for non-muscle-invasive bladder cancer. Patient and methods: A Caucasian male, aged 76 years, exposed to bacillus Calmette-Guérin for a high-grade non-muscle-invasive bladder cancer in 2015, reported painful and progressive left scrotal swelling with purulent discharge from a cutaneous fistulous track that yielded, on liquid culture, a pan-susceptible Mycobacterium tuberculosis hominis strain. Moreover, after 6 months of anti-tuberculosis treatment, an abdominal peri-aortic mass, sized 4 cm, was found and a surgical biopsy showed necrotizing granulomas; however, although smear microscopy and Xpert MTB/Rif™ performed on fresh biopsy sample were positive, liquid cultures resulted negative, indicating treatment efficacy. Results: Numerous peculiar and multi-organ involvement due to BCGitis after intravesical immunotherapy have been previously described, including 17 scientific articles about epididymitis, however, no reports so far showed reactivation of Mycobacterium tuberculosis hominis after bacillus Calmette-Guérin treatment. Conclusion: Although BCGitis is more prevalent in patients undergoing bacillus Calmette-Guérin instillation for non-muscle-invasive bladder cancer, tuberculosis by other species of Mycobacterium tuberculosis should be always ruled out by molecular and conventional microbiology in patients with a history of Mycobacterium tuberculosis hominis exposure.